ANALISIS URUTAN NUKLEOTIDA 0,3 KB GEN ND2 DAN GEN COI DNA MITOKONDRIA MANUSIA INDONESIA - Wayan Suma, I
Abstract: Human mtDNA genome organization is very simple (16,569 kb with a total of 37 genes), however it is unique in having a high polymorphism compared to nuclear DNA. In this context, we have performed research work about nucleotide sequences analysis of Indonesian human mtDNA especially at nucleotide sites 5,042-5,341 (0.3 kb of ND2 gene) and at nucleotide sites 6,085-6,384 (0.3 kb of COI gene). The research is a part of URGE project about \"Normal Variant Data Base of the Indonesian Human Mitochondrial DNA and Translational Products\". The problem of the research has focused on how nucleotide sequences of Indonesian human mtDNA especially nucleotide sites 5,042-5,341 and 6,085-6,384 compared to the Cambridge sequence as a standard reference. A Method has been developed in this research for mouth epithelial cells lysis without mtDNA isolation. Amplification of mtDNA template by PCR with a pair primers of XI and X2 was to performed amplify a 1.3 kb PCR fragment of mtDNA at nucleotide sites 5,042-6,384. Then the PCR fragment was cloned in to E. coli JM109 cells and sequenced with dye terminator labeling method. The total bases that were sequenced was 600 base of each sample from nine of normal Indonesian human. The results of homology analysis with pairwise aligned sequence were eleven substitutions of normal nucleotide variants in ten nucleotide polymorphic sites compared to the Cambridge sequence as a standard reference. All the substitutions were new variants that never published by other researchers. Five of them were transition substitutions and six of the others were transversion substitutions. All of transversion substitutions plus one of transition substitutions were nonsynonymous substitutions that caused seven variants of amino acid translational products and four transition substitutions of the others were synonymous substitutions or silent substitutions. Average divergence estimated were 0,11% and 0,73% for 0.3 kb of ND2 and 0.3 kb of COI genes, respectively. These were smaller than estimate value of divergence of D-loop of normal Indonesian human mtDNA.